STRATEGI IMPLEMENTASI PROGRAM EKOWISATA DI KOTA MANADO - LAMADAU, SRI NANDA; Lengkong, Florence Daicy; Dengo, Salmin (Sam Ratulangi University, 2017)
The implementation of the regional autonomy law in force since 1999, actually had the basicconcept based on potential, preferences, and the aspirations of a democratic secarah area with include therole of the local community. one of the potential development and natural resource conservation throughecotourism which is a form of tourism that very closely with the principles of conservation, even in thedevelopment strategy of ecotourism is also using the strategy of conservation, ecotourism is thus very preciseand berdayaguna in maintaining the integrity and authenticity of the ecosystems in the area. Therefore,who became the Program's Implementation Strategy is the research of ecotourism in the city of Manado.This research uses Qualitative Research Methods using SWOT analysis. Analysis of internalfactors of yield factors of strength and weakness. Strength (Strenghts). the potential Natural touristdestinations, training or training for the improvement of HUMAN RESOURCES, Event or activity sectorof tourism, the presence of public awareness related to tourism, and the creation of access roads to thetourist destinations. Factors of weakness (Weakness), namely the lack of budget, lack of capital/humanresources expert at bidannya, Less the maximum transport facilities and infrastructure, the presence ofbeach reclamation in the Bay of manado, the lack of a Government policy or regulation that sustainprograms of ecotourism. External factors the factors generating opportunities and threats. A factor ofopportunity (Opportunities) that the development of information and technology, the growth of hotels andinns, and the presence of investment from outside. Factor threats (Threats), namely the existence of touristdestinations elsewhere, Adanaya negative issues in the city of Manado, and the existence of a naturaldisaster.Based on the SWOT analysis, the set of six strategies, namely: increase in the productivity of thetourism sector, increased promotion and competitiveness of the tourism sector, the development potential ofthe natural tourist destinations and the improvement of the management of access to information, openspace cooperation with investors, create a policy that supports the implementation of development in thefield of tourism, human resources and recruiting experts in the field of tourism development.Keywords: implementation strategies of ecotourism in Manado city, the SWOT.